2021
DOI: 10.1186/s13059-020-02222-w
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genomic and transcriptomic analysis reveals unique characteristics of hepatic metastases and pro-metastatic role of complement C1q in pancreatic ductal adenocarcinoma

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal cancers due to its high metastasis rate in the liver. However, little is known about the molecular features of hepatic metastases due to difficulty in obtaining fresh tissues and low tumor cellularity. Results We conduct exome sequencing and RNA sequencing for synchronous surgically resected primary tumors and the paired hepatic metastases from 17 hepatic oligometastatic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 74 publications
7
38
0
Order By: Relevance
“…However, a common pattern of sub-type expression among the genes was observed in KIRC, LUAD, LUSC, and STAD. This pattern of gene expression is in alignment with the literature demonstrating the context-dependent expression and functions of complement components in different types of cancer [26,[46][47][48][49][50][51].…”
Section: Discussionsupporting
confidence: 88%
“…However, a common pattern of sub-type expression among the genes was observed in KIRC, LUAD, LUSC, and STAD. This pattern of gene expression is in alignment with the literature demonstrating the context-dependent expression and functions of complement components in different types of cancer [26,[46][47][48][49][50][51].…”
Section: Discussionsupporting
confidence: 88%
“…This mechanism, possibly important for effective immune response, may play a key role in pNETs and highlight potential therapeutic targets to invigorate efficient immune response. Recently, Yang et al reported compelling results about the potential involvement of the complement C1q activation in liver metastasis of patients with pancreatic adenocarcinomas [ 54 ]. Moreover, they showed that C1q is mainly expressed at tumor stroma rather in tumor cells and is involved in complement cascade.…”
Section: Discussionmentioning
confidence: 99%
“…In a KRAS-mutated murine PDAC cell model, tumor-intrinsic CXCL1 expression alone determines the quantitative and qualitative features of infiltrative CD8 + T cells and hence response to checkpoint immunotherapy [41]. In addition, after successfully metastasizing to a distant organ, PDAC cells establish a new TME that is remarkably similar to the primary tumor, featuring a highly fibrotic stroma, heavy infiltration of suppressive myeloid cells, and exclusion of cytotoxic T cells [42,43]. The intense desmoplastic histologic feature is not a cardinal feature of other KRAS-mutant cancer types such as non-small cell lung cancer (NSCLC), colorectal cancer, (CRC) or multiple myeloma.…”
Section: Forward Circuitry: Oncogenic Kras Drives Inflammatory Cytokines To Shape the Tmementioning
confidence: 99%